The Use of Smart TV in Teaching English: A Case Study at Senior High Schools in Watampone - Masdar, Zulfikar; Yauri, Andi Muhammad; Hidayat S, LD. Dian; Nur, Hasriati; Musfirah (DIDAKTIKA, 2025)
This study aims to describe the benefits and roles of Smart TV in teaching English at Indonesian senior high schools. The Smart TV in this study refers to digital technology provided by the Ministry of Education under the Smart School Program, which was initially implemented during the Covid-19 pandemic and is now integrated into regular classroom activities. This qualitative research employed a case study design involving three English teachers from different senior high schools in Watampone. The data were collected through interviews and classroom observations. The findings reveal that the use of Smart TV offers several benefits in English teaching, including fostering students’ engagement, enhancing their interest and motivation, and improving classroom interaction. In addition, Smart TV serves as an effective learning resource that provides teachers with easier access to teaching materials and enables the use of audiovisual content to support language comprehension. Observations confirmed that Smart TV promotes more dynamic, enjoyable, and technology-oriented learning environments. The study concludes that Smart TV plays a significant role in supporting teachers’ pedagogical practices and students’ learning experiences, suggesting its potential for wider integration in language classrooms.